Design and Analysis of Routing Protocols for the Internet of Drones - Bine, Lailla M. S.; Ruiz, Linnyer B.; Loureiro, Antonio A. F. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2024)
The Internet of Drones (IoD) is an emerging technology enabling a new era of drone services and applications. However, many barriers and challenges remain until it is possible to control a complex IoD network. The scientific community is still discussing, studying, and investigating the best way to implement this network to become the IoD viable, reliable, and efficient. Furthermore, the principles that guide terrestrial wireless networks and even traditional Unnamed Aerial Vehicles (UAV) networks do not apply to IoD mainly because it allows distinct drones performing different applications to share the airspace. This thesis aims to provide procedures and discussions that can guide future development to overcoming barriers related to fundamental problems in IoD, such as communication and mobility.